Methicillin-resistant Staphylococcus aureus (MRSA) in a tertiary surgical and trauma hospital in Benghazi, Libya - Buzaid, Najat; Elzouki, Abdel-Naser; Taher, Ibrahim; Ghenghesh, Khalifa Sifaw (The Journal of Infection in Developing Countries, 2011)
Introduction: Methicillin resistant Staphylococcus aureus (MRSA) is a multidrug resistant organism that threatens the continued effectiveness of antibiotics worldwide and causes a threat almost exclusively in hospitals and long-term care settings. This study investigated the prevalence of MRSA strains and their sensitivity patterns against various antibiotics used for treating hospitalized patients in a major tertiary surgical hospital in Benghazi, Libya. Methodology: We investigated 200 non-duplicate S. aureus strains isolated from different clinical specimens submitted to the Microbiology Laboratory at Aljala Surgical and Trauma Hospital, Benghazi, Libya from April to July 2007. Isolates were tested for methicillin resistance by the oxacillin disc-diffusion assay according to Clinical and Laboratory Standards Institute guidelines. MRSA strains were tested for antimicrobial resistance (i.e., vancomycin, ciprofloxacin, erythromycin, chloramphenicol and fusidic acid) using commercial discs. Information on patient demographics and clinical disease was also collected. Results: Of the isolates examined 31% (62/200) were MRSA. No significant differences were observed in the prevalence of MRSA among S. aureus from females or males or from different age groups. Most MRSA were isolated from burns and surgical wound infections. Antibiotic resistance patterns of 62 patients with MRSA to vancomycin, ciprofloxacin, fusidic acid, chloramphenicol and erythromycin were 17.7%, 33.9%, 41.9%, 38.7% and 46.8% of cases, respectively. Conclusion: MRSA prevalence in our hospital was high and this may be the case for other hospitals in Libya. A sound surveillance program of nosocomial infections is urgently needed to reduce the incidence of infections due to MRSA and other antimicrobial-resistant pathogens in Libyan hospitals.